Optimum Sizing and Performance Assessment of Modified Energy Efficient Jaggery Unit for Economic Self Sufficiency of Farmers in India - Totappa Hasarmani; Rajesh Holmukhe (agriTECH, 2022)
The complete lockdown experienced in India since March 2020 has brought the nation’s economy to a halt, severely impacting the destitute and the most vulnerable, including farmers and migrant laborers. However, the country envisaged the vision of “Atmanirbhar Bharat Abhiyan” (Self-reliant India Movement) on May 12, 2020, that focuses on the importance of promoting local products and encourages manufacturing industries including the agricultural sector. The awareness campaign includes reforms to encourage businesses, attract investments, and strengthen production processes. Agriculture businesses are playing a major role in boosting the economy, such as Jaggery manufacturing, which is one of the most popular food processing enterprises that promotes job openings in rural India. Though, the country is the leading exporter of jaggery to the world, most of the production units, situated in remote places are designed without any scientific base and are seriously facing energy inefficiency problems. This research aims to design and develop a modified energy-efficient jaggery unit for the farmer producer groups, to achieve a “Self-reliant India”. The proposed cost effective “Energy Efficient Jaggery Unit” is self reliant to meet all the requirements of the production process,such as combined heat and power (CHP) with the generation of biofuel, termed as Tri-Generation System.